2008
DOI: 10.1002/hipo.20457
|View full text |Cite
|
Sign up to set email alerts
|

The extended hippocampal‐diencephalic memory system: Enriched housing promotes recovery of the flexible use of spatial representations after anterior thalamic lesions

Abstract: The anterior thalamic (AT) nuclei constitute an important component of an extended hippocampal-diencephalic system, and severe persisting memory deficits are normally found after AT damage. This study examined whether postoperative enrichment promotes the recovery of the flexible use of spatial representations in rats with AT lesions. After training to swim from a single constant start position to a submerged platform in a Morris water maze, rats with AT lesions that were housed in standard cages (AT-Std) perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 75 publications
0
24
0
1
Order By: Relevance
“…However, they can eventually catch up with controls over prolonged testing. Nevertheless, subsequent probe trials revealed a disproportionately impaired performance on trials with the new start points, showing that these rats are unable to use learned information in occurrences differing from past experience, that is, to make flexible use of spatial representations (Wolff et al, 2008b). These studies therefore point to a major and specific role for the anterior thalamus in spatial navigation, especially when distal cues are essential for successful performance.…”
Section: The Anterior Thalamus and Hippocampal Functionsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, they can eventually catch up with controls over prolonged testing. Nevertheless, subsequent probe trials revealed a disproportionately impaired performance on trials with the new start points, showing that these rats are unable to use learned information in occurrences differing from past experience, that is, to make flexible use of spatial representations (Wolff et al, 2008b). These studies therefore point to a major and specific role for the anterior thalamus in spatial navigation, especially when distal cues are essential for successful performance.…”
Section: The Anterior Thalamus and Hippocampal Functionsmentioning
confidence: 80%
“…In the same vein, when training in the water maze is conducted with a single, constant start point, rats with hippocampal system damage exhibit substantial improvement throughout training to the extent that they hardly differ from Sham rats (Eichenbaum, 2000;Eichenbaum et al, 1990). ATN rats, however, show a severe deficit even during the initial acquisition phase (Wolff et al, 2008b), which suggests that the loss of HD cells deeply affect virtually any spatial strategy. Thus, efficient spatial navigation resulting from the integration of both idiothetic and allocentric cues (Yoganarasimha and Knierim, 2005) may also be facilitated by the dynamics of the HD signal (Valerio and Taube, 2012).…”
Section: Specific Functions Of the Anterior Thalamusmentioning
confidence: 99%
“…The AD and AV nuclei have been reported to be involved in spatial learning and memory, and navigation; however, these nuclei are not the sole contributors, but rather work in conjunction with the other anterior thalamic nuclei to achieve these functions (Segal et al, 1988;van Groen et al, 2002;Oda et al, 2003;Wolff et al, 2008). It is difficult to hypothesize on the potential effect of the presence of cholinergic neurons within and closely surrounding these nuclei in regards to function; but given that the cholinergic system in general appears to be related to activity requiring both alertness and awareness, these neurons may have the effect of enhancing the wakefulness promoting functions of the anterior thalamic nuclei in the hyrax, possibly leading also to enhanced learning and memory functions.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the IL thalamus (as well as MD/IMD) do not appear to participate in hippocampal-dependent functions, but rather are involved in prefrontal cortical-associated behaviors. Specifically, IL or MD lesions produce little or no alteration on tasks involving spatial memory (Hunt and Aggleton 1998a;Bailey and Mair 2005;Mitchell and Dalrymple-Alford 2005;Wolff et al 2008), but severely disrupt performance on 'prefrontally associated' tasks, or those requiring shifts in strategy or behavioral flexibility (Beracochea et al 1989;McAlonan et al 1993;Hunt and Aggleton 1998b;Lacroix et al 2002;Floresco et al 2008;Ghods-Sharifi et al 2008;Dolleman-van der Weel et al 2009). The pronounced 5-HT input to IL and MD/IMD could serve to coordinate the activity of medial affective (CM and IMD) and lateral motor (PC, CL and lateral MD) components of these systems, thereby providing emotional drive for complex motor acts.…”
Section: Comparisons With Previous Examinations Of 5-ht Innervation Omentioning
confidence: 99%